Financial Innovation, Payment Choice and Cash Demand – Causal Evidence from the Staggered Introduction of Contactless Debit Cards - Martin Brown; Nicole Hentschel; Hannes Mettler; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2020)
We examine how an innovation in payment technology impacts on consumer payment choice and cash demand. We study the staggered introduction of contactless debit cards between 2016-2018. The timing of access to the contactless technology is quasi-random across clients, depending only on the expiry date of the existing debit card. Our analysis is based on administrative data for over 21'000 bank clients and follows a pre-analysis plan. Average treatment effects show that the receipt of a contactless card increases the use of debit cards especially for small-value payments. However, we find only a moderate average reduction in the cash share of payments and no reduction of average cash demand. Treatment effects on payment choice are strongest among consumers with an intermediate pre-treatment use of cash. Explorative analyses reveal that effects are largely driven by young consumers in urban locations.
Keywords: E41; G20; O33; D14; 330; Financial innovation; cash; money demand; payment choice; pre-analysis plan